2021
DOI: 10.1371/journal.pone.0245906
|View full text |Cite
|
Sign up to set email alerts
|

School policies and practices associated with Thai children’s overall and domain specific physical activity

Abstract: School has a significant role in providing opportunities for children to engage in physical activity (PA) through policies and practices. This study aimed to identify the prevalence of school policies and practices related to physical activity (PA) and their association with Thai students’ overall and domain specific PA. This cross-sectional analysis included 5,830 students aged 6–17 years from 136 schools recruited though a multi-stage stratified cluster sampling across Thailand. Student’s PA data were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The U4HK strategy showed improvements in schoolchildren's physical activity beyond what Amornsriwatanakul et al reported with the strategy they implemented in schoolchildren aged six through 17 in Thailand (16). Similarly, this study highlights the need to sponsor physical activity through public policy; this would make it possible to promote it outside of school settings.…”
Section: Discussionsupporting
confidence: 43%
“…The U4HK strategy showed improvements in schoolchildren's physical activity beyond what Amornsriwatanakul et al reported with the strategy they implemented in schoolchildren aged six through 17 in Thailand (16). Similarly, this study highlights the need to sponsor physical activity through public policy; this would make it possible to promote it outside of school settings.…”
Section: Discussionsupporting
confidence: 43%
“…Recent evidence from Thailand also indicated that, though physical activity policies did not translate into students' physical activity levels except for active transportation, most schools (87.5% of 136 schools) reported having several physical activity-related policies and practices. 29 In LIC, behavioral/individual indicators were correlated with some climate change indicators but not with the 2 economic factors. Specifically, annual temperature and/or precipitation were negatively correlated with Overall Physical Activity, Active Play, and Active Transportation in LMIC.…”
Section: Results From Lmicmentioning
confidence: 94%
“…The lower level of PA among primary school students could be attributed to policies and practices in primary schools that currently prioritize infrastructure development at the expense of facilities for PA. While most schools have policies to support PA equipment and sports facilities, only about one-third of schools have a recess policy [ 58 ]. What is more, the standard Thai primary school curriculum prescribes an average of only 40 min of physical education per week, in contrast with a long duration of daily classroom learning (from 8:00 a.m. to 3:30 p.m.), which is predominantly in the sitting position.…”
Section: Discussionmentioning
confidence: 99%